2005
DOI: 10.1016/j.orthres.2005.03.022.1100230622
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous three-dimensional strain fields during unconfined cyclic compression in bovine articular cartilage explants

Abstract: Articular cartilage provides critical load-bearing and tribological properties to the normal function of diarthrodial joints. The unique properties of cartilage, as well as heterogeneous deformations during mechanical compression, are due to the nonuniform microstructural organization of tissue components such as collagens and proteoglycans. A new cartilage deformation by tag registration (CDTR) technique has been developed by the authors to determine heterogeneous deformations in articular cartilage explants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Explant studies have shown that transverse strains are tensile and maximal at the articular surface [18, 26, 27]. In contrast, the transverse strains in this study, which were normalized to the depth of the cartilage, showed maxima at the tibial subchondral interface (Figure 5) and within the thickness of the femoral cartilage, although transverse strains at all levels of depth were similar.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Explant studies have shown that transverse strains are tensile and maximal at the articular surface [18, 26, 27]. In contrast, the transverse strains in this study, which were normalized to the depth of the cartilage, showed maxima at the tibial subchondral interface (Figure 5) and within the thickness of the femoral cartilage, although transverse strains at all levels of depth were similar.…”
Section: Discussioncontrasting
confidence: 72%
“…In newborn bovine cartilage explants compressed between porous platens, axial strains were highest at the superficial zone and decreased nonlinearly through a 1-mm layer of cartilage [9], although the full cartilage depth was not investigated. Other studies have demonstrated maximal strains in the loading direction at the articular surface of juvenile [26, 27] and adult bovine articular cartilage [26]. Another study showed axial compressive strains to be maximal in the middle of the full-thickness young bovine cartilage [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carbon fiber piston on glass) pneumatic cylinder. This configuration allowed for load-controlled compression cycles to be applied to constructs with millisecond timing precision (Neu et al 2005). Biochemical studies (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue deformation measures through the 3D volume of cartilage are based on tag registration (Neu et al 2005) and phase contrast (Neu and Walton 2008) methods. These techniques provide a local measure of deformation to a high (e.g.…”
Section: Introductionmentioning
confidence: 99%